2011
DOI: 10.1128/jvi.00215-11
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecules Targeting Hepatitis C Virus-Encoded NS5A Cause Subcellular Redistribution of Their Target: Insights into Compound Modes of Action

Abstract: Hepatitis C virus (HCV) is a global health concern; recent estimates suggest that 2.2 to 3% of the world's population, equivalent to 130 to 170 million individuals, are chronically infected with the virus (13, 31). These patients are at risk of developing debilitating liver diseases such as cirrhosis and hepatocellular carcinoma (1). Furthermore, current models suggest that the burden of HCV-associated disease is set to rise for the next 20 years (6). There is no HCV vaccine; the current standard of care (SOC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
121
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(140 citation statements)
references
References 67 publications
11
121
1
1
Order By: Relevance
“…A recent study showed that both Domains I and II of NS5A exhibit RNA binding activities (20). However, the ability to bind specifically to uridine-and guanosine-rich RNA resides in domain I and the adjacent linker region (33). An alternative structure of Domain I has been determined that is also dimeric in nature, although the interface lacks the large groove or any obvious RNA interaction surface (31).…”
Section: Hepatitis C Virus (Hcv)mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study showed that both Domains I and II of NS5A exhibit RNA binding activities (20). However, the ability to bind specifically to uridine-and guanosine-rich RNA resides in domain I and the adjacent linker region (33). An alternative structure of Domain I has been determined that is also dimeric in nature, although the interface lacks the large groove or any obvious RNA interaction surface (31).…”
Section: Hepatitis C Virus (Hcv)mentioning
confidence: 99%
“…The dimer is oriented in such a way that a large groove exists between the two monomers and has been proposed as an RNA binding site (29). NS5A has RNA binding activity that requires a dimer based on glutaraldehyde-cross-linking experiments (30,33). Unfortunately, a connection between the NS5A RNA binding activity and a specific aspect of RNA replication or virion assembly remains to be established (30).…”
Section: Hepatitis C Virus (Hcv)mentioning
confidence: 99%
“…12 In this context, it is noteworthy that preformed replication complexes (RCs) are refractory to inhibition of HCV RNA replication by NS5A inhibitors. [12][13][14] Furthermore, NS5A inhibitors have been shown to induce redistribution of NS5A from endoplasmic reticulum-derived foci, [12][13][14] possibly to lipid droplets, 12 and limit hyperphosphorylation of NS5A, [14][15][16] although these effects may be indirect. Finally, it has been suggested that NS5A inhibitors may disrupt interactions of NS5A with HCV RNA, other viral proteins, and/or host factors that are coopted by NS5A during the HCV life cycle.…”
Section: Hcv Ns5a Inhibitors Disrupt Replication Factory Formation: Amentioning
confidence: 99%
“…In this context, the class-defining resistance site Y93 is located at opposing, membrane-proximal surfaces of the dimer interface for both "back-to-back" and "clam-like" alternative domain I (genotype 1b) crystal structures. 10,11 Third, biotin-tagged DCV derivatives enable precipitation of NS5A from pretreated HCV replicon-harboring cells, 6,12 although interestingly fail to precipitate NS5A from replicon lysates or pretreated NS5A-overexpressing cells. 12 In this context, it is noteworthy that preformed replication complexes (RCs) are refractory to inhibition of HCV RNA replication by NS5A inhibitors.…”
Section: Hcv Ns5a Inhibitors Disrupt Replication Factory Formation: Amentioning
confidence: 99%
See 1 more Smart Citation